Promotion of novel plant-based dishes among older consumers using the 'dish of the day' as a nudging strategy in 4 EU countries. (July 2019) - Zhou, Xiao; Perez-Cueto, Federico J.A.; Dos Santos, Quenia; Bredie, Wender L.P.; Molla-Bauza, Margarita Brugarolas; Rodrigues, Vanessa Mello; Buch-Andersen, Tine; Appleton, Katherine M.; Hemingway, Ann; Giboreau, Agnès; Saulais, Laure; Monteleone, Erminio; et al.
Highlights: Pan-EU study on the effect of 'dish-of-the-day' nudge strategy on older consumers. Nudging by 'dish-of-the day' did not influence older people's plant-based dish choice. Gender, country, sensory dimension, universalism and security influenced choice. Improved dietary quality for older consumers requires combination of strategies. Abstract: A quasi-experimental study was designed to promote novel plant-based dishes using the nudging strategy 'dish of the day' among older consumers in Denmark, France, Italy and the United Kingdom. Participants were presented with three dish options: veggie balls, meatballs and fish cakes. In the intervention situation, participants were informed that the 'dish of the day' was the novel plant-based 'veggie balls'. Thereafter, participants were asked to choose one of three dishes to intake and then fill a questionnaire. No statistically significant difference in dish choice was found between the control group and intervention group in the four countries. Males were less likely to choose the plant-based dish when compared with the females. Participants from the United Kingdom and Denmark were more likely to choose the plant-based dish when compared with participants from France. High scores of security dimension from the Human Value Scale was negatively associated with choice of plant-based dish, while high scores of the sensory dimension from Food Choice Questionnaire and high scores of the universalism dimension from Human Values Scale were positively related to the choice of the plant-based dish. The 'dish of the day' nudging approach did not influence older people's plant-based dish choice. Gender, country, and dimensions of sensory, universalism and security were critical factors influencing an older people's plant-based food choice.